Abbasi halifesi El-Kaim Biemrillah ve dönemi(1031 - 1075) - Kaymak, Suat (My University, 2014)
Bu çalışmada, ‘Abbâsî Halifesi el-Kâ’im bi-Emrillâh ve dönemi (1031-1075) incelen-mektedir. el-Kâ’im bi-Emrillâh’ın dönemi ‘Abbâsî, Buveyhî, Selçuklu ve Fâtimî ilişkileri bakımından oldukça önemlidir. Dönemin ilk yirmi dört yılında Buveyhîlerin, sonrasında Sel-çukluların Bağdâd’a hâkim olduğu görülmektedir. ‘Abbâsî tarihinde el-Kâ’im bi-Emrillâh dönemi, ilk ‘Abbâsî-Selçuklu münasebetleri, ‘Irâk Buveyhîlerinin yıkılışı, Selçukluların ‘Irâk’a hâkim olması ve Arslan el-Besâsîrî hadisesi bakımından da önemli yere sahiptir. Özellikle Halife’nin el-Besâsîrî tarafından esir edilmesi ve sonrasında Tuğrul Bey’in el-Kâ’im bi-Emrillâh’ı kurtarmasıyla hilâfetin çöküşün eşiğinden dönmesi ‘Abbâsî tarihinin dönüm nokta-larından biridir. Yine ‘Abbâsî ve Selçuklu hanedanları arasında yapılan evliliklerin de büyük bir önem taşıdığı görülmektedir. Emrillâh, ‘Abbâsîler, Buveyhîler, Selçuklular, Fâtimîler, Tuğrul Bey, Alp Arslan, İbrâhîm Yinâl, Arslan el-Besâsîrî.

In this study, the ‘Abbāsid Caliph al-Qā’im bi-Amr Allāh and his period (1031-1075) were examined. The reign of al-Qā’im bi-Amr Allāh is a significant era for the ‘Abbāsid relations between the Buwayhids, the Fātimides, and The Great Saljukids. In the first twenty four years of his long reign, the Buwayhids controlled Baghdad which was followed by the Saljukids’ conquest and rule. Additionally, the reign of al-Qā’im has an importance in terms of the first ‘Abbāsid relationships with the Saljukids and the Saljukids’ domination in ‘Irāq. Moreover, fall of the Buwayhids of Iraq and the incident of Arslan al-Basāsīrī are the other significant occurrences of his era. Particularly, the Caliph’s captivity by al-Basāsīrī and Toghrïl Beg’s successful attempt to rescue the Caliph marked a watershed in the ‘Abbāsid history. Nevertheless, the intermarriages between the ‘Abbāsid and the Saljukids dynasties played an important role in this period. Amr Allāh, ‘Abbāsid, Buwayhids, Saljukids, Fātimides, Toghrïl Beg, Alp Arslan, Ibrāhīm Yināl, Arslan al-Basāsīrī.
Keywords: Abbasiler; Abbâsîler; Alp Arslan; Arslan el-Besâsîrî; Buveyhîler; Fâtimîler; Irak; İbrâhîm Yinâl; Selçuklular; Tuğrul Bey; Türk Tarihi